The value of intrapartum ultrasound in predicting mode of delivery: A prospective cohort study - Omar, Gamal; Marwa F Sharaf; Mohammad A. Taymour (Indonesian Journal of Obstetrics and Gynecology, 2024)
Abstract Objectives: Ultrasound contributes significantly to management of labor, delivery and prevention of adverse maternal and fetal outcomes. Among many suggested intra-partum ultrasound parameters, the use of transperineal ultrasound scan to assess the angle of progression (AoP) and levator hiatus anteroposterior diameter (APD) has been suggested to result in a more objective evaluation of labor progress. The aim of this study was to assess this claim. Methods: This was a prospective observational cohort study involving primparous term singleton vertex presentation pregnant patients >18 years old admitted in the first stage of labor between January 2021 and May 2023. All patients provided an informed written consent. This investigation utilized both transabdominal and transperineal ultrasonography for comprehensive fetal and pelvic floor assessment. Transabdominal ultrasound evaluated standard parameters including fetal occiput position, biometry number, viability, presentation, and estimated fetal weight. Intrapartum transperineal ultrasonography, specifically performed during the first stage of labor, focused on the Levator Hiatus, measuring its anteroposterior diameter (APD) at rest and during Valsalva maneuver, as well as the angle of progression (AOP). Results: The study population comprised 609 participants with a mean age of 22.8 ± 4.3 years and a high prevalence of being overweight and obesity (38.8% and 57.8%, respectively). When comparing patients who had an intrapartum CS to those who had a normal vaginal delivery (NVD). However, on logistic regression, age, BMI, gestational age, posterior occiput presentation, head circumference (HC), AOP (V) and APD (V) as significant predictors for both ICS and 2nd stage CS (p<0.05). Conclusion: This study demonstrated that maternal age, BMI, gestational age, occiput posterior position, Angle of progression at Valsalva and levator hiatus anteroposterior diameter at Valsalva were independent significant predictors for Intrapartum cesarean section in primiparous women at term When the ratio between HC/APD at rest, BPD/APD at Valsalva and HC/APD at Valsalva is high, while the APD at Valsalva, AoP Valsalva values are low, cesarean section was more likely to be the mode of delivery. Keywords: Intrapartum ultrasound, angle of progression, anteroposterior diameter of levator hiatus, mode of delivery, intrapartum cesarean section.